Video subtitle to teach listening skill of junior high school students - Mustofa, Mutmainnah; Sari, Ani Sukma (Universitas Muhammadiyah Sidoarjo, 2020)
A considerable interest on Information and Communication Technology (ICT) has been growing in the field of English language teaching within a very short period of time. Indeed, ICT is such an essential part in the respective field, in the sense that its progress allows the development of language teaching and learning process through its innovations. This study proposes using video caption as a medium to teach listening skill through integrating the use of ICT with the teaching process. An example of the innovation is the creation of teaching media supported by a software or application called . A well-known subtitle editing program, offers source tools for creating and modifying subtitle in a video. This paper presents the procedures and steps to design video subtitle by using application. Teachers can use it as a reference in designing a teaching media using a video subtitling application which is aimed to make the students more motivated to learn English instructions. Last but not least, it is expected that learning with video caption can be an alternative and beneficial media for teaching, in particular, listening skill.